2018
DOI: 10.3390/ijms19113329
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Glutathione Peroxidase (GPX) Gene Family in Rhodiola crenulata and Gene Expression Analysis under Stress Conditions

Abstract: Glutathione peroxidases (GPXs) are important enzymes in the glutathione-ascorbate cycle for catalyzing the reduction of H2O2 or organic hydroperoxides to water. GPXs play an essential role in plant growth and development by participating in photosynthesis, respiration, and stress tolerance. Rhodiola crenulata is a popular traditional Chinese medicinal plant which displays an extreme energy of tolerance to harsh alpine climate. The GPXs gene family might provide R. crenulata for extensively tolerance to environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Further, GPX enzyme and GPX genes also contribute to several plant physiological, biochemical, and molecular mechanisms to withstand harsh environmental stresses [ 5 , 6 ]. In the recent past, GPX gene families have been reported in numerous crop plants, including five GPX genes in date palm ( Phoenix dactylifera L.) [ 51 ] and in Rhodiola crenulate [ 52 ]; six genes in cucumber ( Cucumis sativus L.) [ 53 ], watermelon ( Citrullus lanatus L.) [ 54 ], and Lotus japonicus [ 55 ]; seven genes in sorghum ( Sorghum bicolor L.) [ 19 ]; eight genes in Thellungiella salsuginea [ 56 ] and peach fruit ( Prunus persica L.) [ 57 ]; 13 genes in cotton ( Gossypium hirsutum L.) [ 58 ]; and 14 genes in bread wheat [ 59 ]. To the best of our knowledge, the GPX gene family was yet to be reported in rapeseed that responds to multiple stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Further, GPX enzyme and GPX genes also contribute to several plant physiological, biochemical, and molecular mechanisms to withstand harsh environmental stresses [ 5 , 6 ]. In the recent past, GPX gene families have been reported in numerous crop plants, including five GPX genes in date palm ( Phoenix dactylifera L.) [ 51 ] and in Rhodiola crenulate [ 52 ]; six genes in cucumber ( Cucumis sativus L.) [ 53 ], watermelon ( Citrullus lanatus L.) [ 54 ], and Lotus japonicus [ 55 ]; seven genes in sorghum ( Sorghum bicolor L.) [ 19 ]; eight genes in Thellungiella salsuginea [ 56 ] and peach fruit ( Prunus persica L.) [ 57 ]; 13 genes in cotton ( Gossypium hirsutum L.) [ 58 ]; and 14 genes in bread wheat [ 59 ]. To the best of our knowledge, the GPX gene family was yet to be reported in rapeseed that responds to multiple stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…GPX is composed of a series of isozymes (GPX1-8) that catalyze the reduction in H 2 O 2 or organic hydroperoxides to water or corresponding alcohols [ 11 , 20 ]. Among them, GPX2 is a gastrointestinal tract-enriched selenium-containing and GSH-dependent antioxidant enzyme [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, choline monooxygenase ( Bv6_146100_wdro.t1 ) and betaine aldehyde dehydrogenase ( Bv5_116230_ntjn.t1 ), which are involved in the synthesis of betaine [ 45 ]; glutathione peroxidase ( Bv2_044150_kdwp.t1 ), ferrochelatase 2 ( Bv2_033330_nrat.t1 ) and soul heme-binding family protein ( Bv4_094190_wifn.t1 ) involved in heme biosynthesis in non-photosynthetic tissues and induced by oxidative stress in photosynthetic tissues to supply heme for defensive hemoproteins. Studies of rhodiola crenulata have shown that glutathione peroxidase can physically interact with specific proteins in multiple pathways which participate in photosynthesis, respiration and stress tolerance [ 46 ]. Further, alpha amylase ( Bv1_021820_ccxs.t1 ) was significantly up-regulated under salt stress, which suggests faster starch degradation by mesophyll cells.…”
Section: Discussionmentioning
confidence: 99%